Perkongsian Pengetahuan di Kalangan Pegawai Pengurusan dan Profesional TLDM - Nor Azmi, Tambi Chek (2009)
The purpose of this study is to investigate the correlation and impact of attitude, ability and motivation towards knowledge sharing among the professional and management officers of Royal Malaysian Navy (RMN). This study also aimed is to determine the level of sharing knowledge among the officers in the RMN. Out of 400 questionnaires distributed, a total of 331 questionnaires were returned. The data was analyzed using ”Statistical Package for Social Science” (SPSS) version 15. The result shows that the levels of knowledge sharing among the RMN officers are high. Analysis using Pearson correlation indicates that all the three factors have a significant correlation with knowledge sharing. In addition, multiple regression analysis shows that only ability and motivation significantly can influence knowledge sharing. Therefore, in order to increase the performance, the RMN should change the perception and attitude of their officers toward knowledge sharing.